EFFICIENCY ANALYSIS OF USING TYPICAL AND ATYPICAL WIND ENERGY INSTALATIONS - TARASENKO, MYKOLA; KOZAK, KATERYNA; OMEIZA, LUKMAN; ZIN, MYROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article analyzes the energy efficiency of typical wind turbines (Savonius, Musgrave, Evans, Darier, Magnus, Lentz) and nontypical wind turbines (carousel-petal, double, powerful wind turbines operating on the basis of the Magnus effect, stationary turbine-type wind turbines, airship wind turbines filled with helium ), Sklyarov wind turbine, wind generators, constructions of various wind energy types installations in terms of axis location - vertically axial or horizontally axial, the limit value of the coefficient of wind energy utilization (СWEU), the influence of the control voltage regulator on the reliability and durability of the wind power plant, effectiveness of using confusors and guides for increasing the energy of the wind flow, the efficiency of compact derivative gears and flying wind generators, protection against lightning and overvoltage’s and noise, coefficient of wind flow inhibition etc. It also has been analyzed the effectiveness of the shape of the wind wheel blade and the rotor, the influence of the average annual wind speed and the equivalent number of hours of nominal power generation on the decision-making on the installation of powerful wind turbines, the influence of the number of blades on the speed, the energy efficiency of the wind energy installation of the Sheer Wind company, Air Grey and stationary wind generators, protection against lightning and overvoltage, an approximate determination of the capacity of any wind power plant. It has been established that the speed of the rotor rotation in wind turbines of similar power differs by several times. The number, width, and length of the blades of classic wind turbines with a horizontal axis of rotation and the speed of rotation of the rotor of wind turbines similar in power, which differ by several times, were analyzed.